2011
DOI: 10.1002/cb.342
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and consumer behavior of older adults: A study of subcultural influences in Malaysia

Abstract: Although differences in consumption patterns across countries are often inferred to be the result of different cultural values and religious orientations, they raise issues of validity because of the many country-specific factors that may affect behavior. Furthermore, the effects of religiosity are confounded with those of variables that are associated with religiosity such as age. This paper examines the effects of religiosity on well-being and changes in consumer preferences of 645 adults age 50 and older li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 46 publications
0
87
1
5
Order By: Relevance
“…Relatively few studies to date have identified which customer characteristics might be effective in predicting CSB in developing country mobile markets (e.g., Effah-Bediako et al, 2013;Moschis & Ong, 2011;Yousaf & Malik, 2013). This study hopes to contribute to filling this gap in the literature.…”
Section: Religiosity and Consumer Switchingmentioning
confidence: 93%
See 2 more Smart Citations
“…Relatively few studies to date have identified which customer characteristics might be effective in predicting CSB in developing country mobile markets (e.g., Effah-Bediako et al, 2013;Moschis & Ong, 2011;Yousaf & Malik, 2013). This study hopes to contribute to filling this gap in the literature.…”
Section: Religiosity and Consumer Switchingmentioning
confidence: 93%
“…In the case of the low involvement product category, religiosity negatively influenced the brand consciousness of consumers. In Malaysia, Moschis and Ong (2011) found positive effects of religiosity on well-being but showed that this influence were different across the three main ethnic subcultures of Malaysia (Malays, Indians, and Chinese).…”
Section: Religiosity and Consumer Switchingmentioning
confidence: 96%
See 1 more Smart Citation
“…Religion affects consumers' attitudes, values and behaviors (Khraim, 2010;Moschis & Ong, 2011;Fam, Waller, & Erdogan, 2004). The mystical aspect of the religiosity explains the difficulty to adopt a universal definition of this concept and confines it to the practice of a religion.…”
Section: The Moderating Role Of Religiositymentioning
confidence: 99%
“…Several studies have used religiosity as an antecedent variable that can be used to explain a multitude of behaviors. 14 Of particular interest to religious organizations and non-profi t organizations is its association with charitable giving. A vast number of studies have found a positive relationship between church membership and church attendance with charitable giving.…”
Section: Covariates Of Religiositymentioning
confidence: 99%